HUBUNGAN STATUS RIWAYAT KONTAK BTA+ TERHADAPKEJADIAN TB ANAK(Studi di Balai Kesehatan Masyarakat Wilayah Semarang) - Purnamaningsih, Indah; Martini, Martini; Adi, Mateus Sakundarno; Saraswati, Lintang Dian (Fakultas Kesehatan Masyarakat, 2018)
Tuberculosis (TB) is a disease caused by Mycobacterium tuberculosis and most often infects parts of the lungs. TB in children occurs on 0-14 years old children. This study aimed to prove the relationship between history of contact BTA+ against the incidence of child TB in Community Health Center Semarang area. Analytic observational study design with the type of case control studies used in this study. Samples of pediatric patients aged 0-14 years old were from January 2016 until April 2017. The sample technique using simple random sampling consisted ofÂ 53 case and 53 control. Data analysis using chi-square test. The results showed that there was a correlation between contact history of BTA+ OR = 15.043; 95% CI= 5,808-38,961Â The result of stratification showed nutrition status was confounding on contact history of BTA Children should not sleep with roommate TB BTA+ adults, people always apply the terms of healthy homes,